Race, transnationalism, and nineteenth-century American literary studies - Levine, Robert S. (Robert Steven), 1953- (New York : Cambridge University Press, 2017)
"Inspired by Toni Morrison's call for an interracial approach to American literature, and by recent efforts to globalize American literary studies, Race, Transnationalism, and Nineteenth-Century American Literary Studies ranges widely in its case-study approach to canonical and non-canonical authors. Leading critic Robert S. Levine considers Cooper, Hawthorne, Stowe, Melville, and other nineteenth-century American writers alongside less well known African American figures such as Nathaniel Paul and Sutton Griggs. He pays close attention to racial representations and ideology in nineteenth-century American writing, while exploring the inevitable tension between the local and the global in this writing. Levine addresses transatlanticism, the Black Atlantic, citizenship, empire, temperance, climate change, black nationalism, book history, temporality, Kantian transnational aesthetics, and a number of other issues. The book also provides a compelling critical frame for understanding developments in American literary studies over the past twenty-five years"--
Chapter 6 â#x80;#x9C;Whiskey, Blacking, and Allâ#x80;#x9D;: Temperance and Race in William Wells Brownâ#x80;#x99;s ClotelChapter 7 Beautiful Warships: The Transnational Aesthetics of Melvilleâ#x80;#x99;s Israel Potter -- Chapter 8 Antebellum Rome: Transatlantic Mirrors in Hawthorneâ#x80;#x99;s The Marble Faun -- Chapter 9 Edward Everett Haleâ#x80;#x99;s and Sutton E. Griggsâ#x80;#x99;s Men without a Country -- Chapter 10 Frederick Douglass in Fiction: From Harriet Beecher Stowe to James McBride -- Notes
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: American literature -- 19th century -- History and criticism; Race in literature; Transnationalism in literature; African Americans in literature; American literature -- African American authors -- History and criticism; Black people in literature; Black nationalism in literature; Littérature américaine -- 19e siècle -- Histoire et critique; Race dans la littérature.; Transnationalisme dans la littérature.; Noirs américains dans la littérature.; Personnes noires dans la littérature.; Nationalisme noir dans la littérature.; LITERARY CRITICISM -- American -- General; African Americans in literature; American literature; American literature -- African American authors; Black nationalism in literature; Black people in literature; Race in literature; Transnationalism in literature; 1800-1899; Criticism, interpretation, etc